Stiffness of a compacted residual soil - Rahardjo, Harianto (2011)
Stiffness or Young's modulus of a compacted residual soil can be obtained from numerical analyses that simulate the shear stress versus horizontal displacement of the soil as obtained from the laboratory direct shear tests. The paper presents the simulated Young's moduli of a compacted residual soil from Bukit Timah Granite as obtained from numerical analyses of direct shear test results on saturated and unsaturated specimens. The Young's modulus of the soil appears to increase with increasing net normal stresses and increasing matric suctions. The effect of increasing matric suction on Young's modulus is found to become less significant at high matric suctions.